Enhancement of Palmarumycin C(12 )and C(13) Production in Liquid Culture of the Endophytic Fungus Berkleasmium sp. Dzf12 by Oligosaccharides from Its Host Plant Dioscorea zingiberensis - Li, Yan (Molecules, 2012)
Three crude oligosaccharides were respectively prepared by acid hydrolysis of three polysaccharides, which were water-extracted polysaccharide (WEP), sodium hydroxide-extracted polysaccharide (SEP) and acid-extracted polysaccharide (AEP) from the rhizomes of Dioscorea zingiberensis. Among the three oligosaccharides, the crude oligosaccharide prepared by acid hydrolysis of WEP was found to be the most efficient elicitor to enhance the production of palmarumycins C(12) and C(13) in liquid culture of endophytic fungus Berkleasmium sp. Dzf12. When OW was applied to the medium at 300 mg/L on day 3 of culture, the maximal yields of palmarumycin C(12) (87.96 mg/L) and palmarumycin C(13) (422.28 mg/L) were achieved on day 15 of culture, which were 9.83 and 3.24-fold in comparison with those (8.95 and 130.43 mg/L) of control, respectively. The results indicate that addition of the oligosaccharides from the host plant D. zingiberensis should be an effective strategy for enhancing production of palmarumycins C(12) and C(13) in liquid culture of endophytic fungus Berkleasmium sp. Dzf12.